Comparison of feature extraction techniques for face verification using elastic graph matching on low-power mobile devices - Nagel, Jean-Luc; Stadelmann, Patrick; Ansorge, Michael; Pellandini, Fausto (My University, 2003)
Biometric face verification using elastic graph matching is considered and two feature extraction techniques used as a pre-processing stage are compared. Low-complexity vs. performance is of particular interest for mobile devices. A modified technique based on a normalization of mathematical morphology feature is introduced and show a performance comparable to that of Gabor features at a much-reduced computational complexity.
Keywords: Biometrics; face verification; feature extraction; graph matching; low-power